Standard Practice in Municipal Accounting and Financial Procedure (Book). - Winter, Sidney G.; Lorig, Arthur N. (The Accounting Review, 1944)
Abstract Reviews the book "Standard Practice in Municipal Accounting and Financial Procedure."